Socio-economic determinants affecting the lifestyle of pregnant women - Fatemeh Estebsari; Farideh Jalili-Bahabadi; Camelia Rohani; Zahra Rahimi Khalifeh Kandi; Davoud Mostafaei (آموزش بهداشت و ارتقاء سلامت ایران, 2020)
Background and Objective: Lifestyle is one of the factors influencing health. The lifestyle of pregnant women undergoes many changes during pregnancy and childbirth. The aim of this study was to identify socio-economic determinants affecting the lifestyle of pregnant women.